2020
DOI: 10.1002/brb3.1923
|View full text |Cite
|
Sign up to set email alerts
|

Association between the frequency of daily intellectual activities and cognitive domains: A cross‐sectional study in older adults with complaints of forgetfulness

Abstract: Cognitive decline is a major problem in aging societies (Alzheimer's Disease International, 2013; Deary et al., 2009). Recently, a range of risk factors related to cognitive decline have been reported, including hypertension, diabetes, social isolation, and less frequent engagement in physical activities (Livingston et al., 2017). Early identification and modification of these risk factors may help prevent or delay the onset of dementia. Because people with complaints of forgetfulness tend to have a higher ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Other studies conducted in Japan, in which the average age of subjects was about 75 yr, showed similar Montreal Cognitive Assessment scores, suggesting that the result reflects old age. 33,34 In this study, since we adopted a diagnostic method for postoperative cognitive dysfunction that has been demonstrated to have excellent sensitivity and specificity in previous studies, 2,14,18 we believe that the relatively low incidence of postoperative cognitive dysfunction after 1 week despite the high percentage (greater than 80%) of patients with preoperative cognitive impairment was not due to a sensitivity issue. Additionally, the incidence of postoperative cognitive dysfunction at 3 months was higher, ranging between 8.5 and 18.4%, depending on the handling of missing data.…”
Section: Discussionmentioning
confidence: 81%
“…Other studies conducted in Japan, in which the average age of subjects was about 75 yr, showed similar Montreal Cognitive Assessment scores, suggesting that the result reflects old age. 33,34 In this study, since we adopted a diagnostic method for postoperative cognitive dysfunction that has been demonstrated to have excellent sensitivity and specificity in previous studies, 2,14,18 we believe that the relatively low incidence of postoperative cognitive dysfunction after 1 week despite the high percentage (greater than 80%) of patients with preoperative cognitive impairment was not due to a sensitivity issue. Additionally, the incidence of postoperative cognitive dysfunction at 3 months was higher, ranging between 8.5 and 18.4%, depending on the handling of missing data.…”
Section: Discussionmentioning
confidence: 81%
“…In addition, our findings suggest that participants who did not watch TV or read were more likely to have poor global cognition. This is not surprising since evidence has illustrated that leisure activities involving brain stimulation, such as watching TV and reading, are protectors of cognition (Iizuka et al, 2021). Although, it should be noted that long hours in front of a TV may contribute to poor cognition, with previous research finding that watching TV for >3.5 h/day by adults aged 50 years or over was related to cognitive decline, particularly a decline in verbal memory (Fancourt & Steptoe, 2019).…”
Section: Discussionmentioning
confidence: 97%
“…Although, the study showed that a decreased perception of one's physical activity may affect unhealthy behavior. But there still has controversial regards group physical exercise or activity in preventing cognitive decline [30][31][32]. Hence, these items mentioned above should be further revisited as dichotomous outcome terms (such as "agree" or "disagree") to the design of the subscale in MCIHB-Q to provide a good t in the subtest [33].…”
Section: Discussionmentioning
confidence: 99%